Reactive oxygen species and anti-proteinases. (1st January 2016) - Siddiqui, Tooba; Zia, Mohammad Khalid; Ali, Syed Saqib; Rehman, Ahmed Abdur; Ahsan, Haseeb; Khan, Fahim Halim
Abstract: Reactive oxygen species (ROS) cause damage to macromolecules such as proteins, lipids and DNA and alters their structure and function. When generated outside the cell, ROS can induce damage to anti-proteinases. Anti-proteinases are proteins that are involved in the control and regulation of proteolytic enzymes. The damage caused to anti-proteinase barrier disturbs the proteinase-anti-proteinases balance and uncontrolled proteolysis at the site of injury promotes tissue damage. Studies have shown that ROS damages anti-proteinase shield of the body by inactivating key members such as alpha-2-macroglobulin, alpha-1-antitrypsin. Hypochlorous acid inactivates α-1-antitrypsin by oxidizing a critical reactive methionine residue. Superoxide and hypochlorous acid are physiological inactivators of alpha-2-macroglobulin. The damage to anti-proteinase barrier induced by ROS is a hallmark of diseases such as atherosclerosis, emphysema and rheumatoid arthritis. Thus, understanding the behaviour of ROS-induced damage to anti-proteinases may helps us in development of strategies that could control these inflammatory reactions and diseases.